Individualized ASO therapy for rare diseases (Communications Medicine, 2023)
Annemieke Aartsma-Rus is a Professor of Translational Genetics at the Leiden University Medical Center. She was one of the pioneers of antisense oligonucleotide (ASO)-mediated exon skipping therapy for Duchenne muscular dystrophy (DMD). Her work focuses on the personalized approach to delivering exon skipping therapy for patients with rare genetic diseases within the setting of the Dutch Center for RNA Therapeutics, which she co-founded in 2020 and is on the Board of Directors. Currently, four exon skipping drugs have been approved by the US Food and Drug Administration for DMD, three of which are based on the IP generated by Aartsma-Rus’ institute. She is also involved in patient education in collaboration with the Duchenne Patient Academy and the European Organisation for Rare Diseases (Eurordis). In this Q&A, we ask Prof. Aartsma-Rus a series of questions on the latest developments in therapies for rare diseases and how best to overcome some of the existing challenges with this endeavour.